2020
DOI: 10.1155/2020/7913418
|View full text |Cite
|
Sign up to set email alerts
|

MiR-181c-5p Promotes Inflammatory Response during Hypoxia/Reoxygenation Injury by Downregulating Protein Tyrosine Phosphatase Nonreceptor Type 4 in H9C2 Cardiomyocytes

Abstract: Background. Constitutive nuclear factor kappa B (NFκB) activation has been shown to exacerbate during myocardial ischemia/reperfusion (I/R) injury. We recently showed that miR-181c-5p exacerbated cardiomyocytes injury and apoptosis by directly targeting the 3′-untranslated region of protein tyrosine phosphatase nonreceptor type 4 (PTPN4). However, whether miR-181c-5p mediates cardiac I/R injury through NFκB-mediated inflammation is unknown. Thus, the present study aimed to investigate the role of miR-181c-5p d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 34 publications
0
14
0
Order By: Relevance
“…Many studies have shown that miR-181c-5p has multiple functions, such as regulating cell apoptosis, inflammation, immunity, and mitochondrial function. MiR-181c-5p could down-regulate PTPN4 to promote the inflammatory response during ischemia/reperfusion injury, and also could regulates ischemia/reperfusion injury-induced neuronal cell death by targeting c-Fos 42 , 43 . Nevertheless, miR-181c-5p remains poorly studied in vascular endothelial cells.…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have shown that miR-181c-5p has multiple functions, such as regulating cell apoptosis, inflammation, immunity, and mitochondrial function. MiR-181c-5p could down-regulate PTPN4 to promote the inflammatory response during ischemia/reperfusion injury, and also could regulates ischemia/reperfusion injury-induced neuronal cell death by targeting c-Fos 42 , 43 . Nevertheless, miR-181c-5p remains poorly studied in vascular endothelial cells.…”
Section: Discussionmentioning
confidence: 99%
“…Further, we also observed an increase in miR-181 in the UB and ILNs of IC mice compared to the control. MiR-181 plays a pro-inflammatory role in hypoxia/reoxygenation injury through non-receptor tyrosine phosphatase 4 (PTPN4) heart cells (32). MiR-181 also regulates T cell-based immune responses via its crucial role in the activation of CD4 + T cells (33).…”
Section: Discussionmentioning
confidence: 99%
“…The cytoplasmic enzyme lactate dehydrogenase (LDH) is released into the cell culture medium from the damaged cells. LDH activity was determined in cell culture supernatant with the use of Cytotoxicity Detection Kit (Roche, Mannheim, Germany) according to the manufacturer's instructions as described [ 34 ]. The absorbance was measured at wavelength of 492 nm with reference wavelength 620 nm.…”
Section: Methodsmentioning
confidence: 99%